Myrtenol Attenuates MRSA Biofilm and Virulence by Suppressing sarA Expression Dynamism - Selvaraj, Anthonymuthu; Jayasree, Thangaraj; Valliammai, Alaguvel; Pandian, Shunmugiah Karutha (Frontiers in Microbiology, 2019)
Methicillin-resistant Staphylococcus aureus (MRSA) is a deleterious human pathogen responsible for severe morbidity and mortality worldwide. The pathogen has attained high priority in World Health Organization (WHO) – Multidrug-resistant (MDR) pathogens list. Emerging MDR strains of S. aureus is clinically challenging due to failure in conventional antibiotic therapy. Biofilm formation is one of the underlying mechanisms behind the antibiotic resistance. Hence, attenuating biofilm formation has become an alternative strategy to control persistent infections. The current study is probably the first that focuses on the antibiofilm and antivirulence potential of myrtenol against MRSA and its clinical isolates. Myrtenol exhibited a concentration-dependent biofilm inhibition without causing any harmful effect on cell growth and viability. Further, microscopic analysis validated the biofilm inhibitory efficacy of myrtenol against MRSA. In addition, myrtenol inhibited the synthesis of major virulence factors including slime, lipase, α-hemolysin, staphyloxanthin and autolysin. Inhibition of staphyloxanthin, in turn sensitized the MRSA cells to healthy human blood and hydrogen peroxide (H2O2). Notably, myrtenol treated cells were deficient in extracellular DNA (eDNA) mediated autoaggregation as eDNA releasing autolysis was impaired by myrtenol. Biofilm disruptive activity on preformed biofilms was observed at concentration higher than minimum biofilm inhibitory concentration (MBIC) of myrtenol. Also, the non-cytotoxic effect of myrtenol on human peripheral blood mononuclear cell (PBMC) was evidenced by trypan blue and Alamar blue assays. Transcriptional analysis unveiled the down-regulation of global regulator sarA and sarA mediated virulence genes upon myrtenol treatment which is well correlated with results of phenotypic assays. Thus, the results of present study revealed the sarA mediated antibiofilm and antivirulence potential of myrtenol against MRSA.